STRATEGI PEMASARAN DAYA TARIK WISATA GUNUNG KELUD DI KABUPATEN KEDIRI, JAWA TIMUR (Jurnal Destinasi Pariwisata, 2026)
Mount Kelud is the only natural attraction in the form of mountains equipped with the beauty of a crater lake. To fully utilize the potential of this tourist area, an effective marketing strategy is needed to increase and optimize the number of tourist visits. This study uses a descriptive qualitative approach. Data collection was carried out through observation, interviews, literature studies, and documentation. The data was then analyzed using three methods, namely data reduction, data presentation, drawing conclusions, and SWOT analysis. This study aims to analyze the constraints of the 7P marketing mix and STP (segmenting, targeting, and positioning) marketing strategies using SWOT analysis on the tourist appeal of Mount Kelud in Kediri Regency, East Java. Through the SWOT analysis method, this study identifies the main strengths of tourist attractions, but there are also challenges that need to be overcome, such as obstacles in the 7P marketing mix that can hinder improvements in marketing performance. From this study, there are several strategies that can be done such as preserve the environment, culture, and man-made attractions, develop thematic tour packages, provide an eco-friendly shuttle bus program, intensify promotions, highlight the uniqueness of attractions and distinctive, improve the quality of tourism services, optimize existing promotions and provide promotional information in multiple languages.